Analysis of the efficiency of hybrid photovoltaic systems implemented by the IPSE in the non-interconnected zones of the department of Guainía - Valencia Llanos, Jairo Alberto; Reyes Viviescas, Danna Liceth (Ingeniería Solidaria, 2022)
Introduction: This article is the product of the research called "Analysis of the efficiency in hybrid photovoltaic systems implemented by the IPSE in the Non-Interconnected Zones of the department of Guainía", a project developed by the Institute for Planning and Promotion of Energy Solutions (IPSE for its abbreviation in Spanish) in the period 2020 to 2021. Problem: The limited availability of energy service delivery hours and the use of a single energy source represented a lack of local energy security, lack of diversification of energy sources, high emissions and energy inefficiency. Objective: Evaluate the energy conversion efficiency of Hybrid Photovoltaic Solar Systems - implemented by IPSE in the Non-Interconnected Zones of the department of Guainía. Methodology: The methodologies used for the evaluation of energy efficiency were: 1) Energy conversion method and form factor for solar panels. 2) Graphical analysis method with efficiency curves for grid-tied and bidirectional inverters. 3) Comparative analysis method between theoretical efficiencies and Specific Fuel Consumption (SFC) for diesel generator sets; and finally, the methodology for calculating the carbon footprint for these last components. Results: For solar panels, the theoretical and actual efficiency were 16.5% and 16.49% with the energy conversion method, and 100% and 78.39% with the form factor method. For inverters linked to the network it was 98.2% and bidirectional 96%; for the generator sets, the efficiency was determined from their fuel consumption with a difference of 2.55 compared to the current standard and Greenhouse Gas emissions on average were 112,465 in standby and 98,417 in prime operating mode. Conclusion: This research has shown that energy efficiency is a key factor for the good performance of energy systems. Originality: This research was conducted by using technical data provided by manufacturers and the own work ’ own analysis.